Development and validation of multi-analyte methods for the determination of migrating substances from plastic food contact materials by GC-EI-QqQ-MS and GC-APCI-QTOF-MS - Kanakaki, Chrysoula; Traka, Theodora; Thomaidis, Nikolaos S. (Frontiers in Sustainable Food Systems, 2023)
The packaging has proven to be a source of some serious food contaminants, with several chemicals migrating from the food contact material into the food. Therefore, efficient means of control of the migration extend and identification of the migrating substances must be established. The necessity of migration tests has been underlined by the European Union (EU) Regulation No. 10/2011, requiring the evaluation of the presence of intentionally and non-intentionally added substances. To facilitate this purpose, highly sensitive, multi-analyte methods are required. Targeting a wide range of volatile migrating compounds, we developed and validated a GC-EI-QqQ-MS and a GC-APCI-QTOF-MS method for the simultaneous determination of 131 and 126 food packaging substances, respectively. Even though the GC-EI-QqQ-MS method presented increased sensitivity for several of the investigated compounds, covering the existing EU requirements and specific migration limits (SMLs) for all targeted analytes; the complementary high-resolution method inherently enables the possibility of further utilization of the obtained raw data among others for retrospective analysis. The applicability of both methods was tested using 95% v/v aqueous ethanol food simulant, representative for the worst foreseeable conditions of intended use for many food contact material applications. Real food packaging samples belonging to different types of plastic materials were tested toward chemical migration, utilizing different migration protocols, depending on the sample characteristics. The favorable analytical features of both methods enable their use for the direct analysis of the investigated food simulant, overcoming the need for sample preparation. Thus, labor intensive and/or time-consuming pre-concentration procedures, which would furthermore restrict the applicability of the methods to certain groups of analytes and add to the uncertainty of the overall results, could be eliminated.